Planning Experience and Planners' Ethics. Issue 2 (3rd April 2017) - Lauria, Mickey; Long, Mellone
Abstract : Problem, research strategy, and findings : Ethical considerations are integral to most aspects of planning, but the bases of planners' ethical decisions are not well understood. In fact, there has been no follow-up to Elizabeth Howe and Jerome Kaufman's original 1979 survey of the ethics of American planners in this journal (45 (3), 243–255). Our research evaluates the differences in planning roles and planners' ethical perspectives since then. In their study, Howe and Kaufman use hypothetical scenarios to determine which of three roles planners play: technician, politician, or a hybrid . They also evaluate how the role that planners assume affects their ethical views. Our research uses similar scenarios to evaluate these relationships in contemporary planning practice while simultaneously evaluating the influence of professional experience on the ethical bases of those choices. We confirm many of Howe and Kaufman's findings, but first we find that today's planners assume different roles than they did in the mid-1970s, conforming more often to a technical role and less to a political or hybrid role. Second, today's planners tend to make virtue-based choices when concerned with ideological and legal issues, but revert to rule-based or utilitarian choices when faced with the dissemination and quality of information and segments of the population receiving special advantages. Finally, we find that planners, at all stages in their careers, maintain a mixture of virtue- and rule-based ethical choices while affirming the profession's core values (as represented in the 2009 AICP Code). Takeaway for practice:  The vast majority of practicing planners in our sample (80%) use the AICP Code of Ethics in response to our hypothetical scenarios. At the same time, self-interested responses were rarely made. These findings reaffirm the code's value to the profession.